Labour Market Skill Deficiencies in The Tourism and Hospitality Industry - Rok, Marija (Naše gospodarstvo/Our economy, 2012)
The Slovenian tourism and hospitality labour market suffers from several deficiencies and structural imbalances. This paper focuses on one solution to these problems in terms of certifications of accredited national vocational qualifications. The tenth anniversary of Slovenia’s adoption of the National Professional Qualifications Act seems a convenient time to evaluate the results of this certification system and meas- ure the benefits. A survey was conducted on a sample of employers in the tourism and hospitality industry. Using quantitative data analysis as well as a correlation and multivariate factor analysis, the major deficiencies in the implementation of the certification system were identified.